A framework for supply chain management of Remdesivir injection using blockchain technology. (6th February 2023) - Kuliha, Arun; Varma, Sunita; Sakle, Mukesh; Kuliha, Megha
The COVID-19 disease has affected the condition of human life in every aspect whether it is social, financial or mental. The virus is spreading all around the world, and needs to be treated as early as possible. In this scenario, the life-saving drug Remdesivir injection plays an important role. The urgent need by patients, high call rate and also price of the Remdesivir injection create counterfeits, black-marketing and hoarding. This research work proposes the use of block chain in a global implementation of supply chain management of Remdesivir injection. Block chain system helps to reduce worldwide concern about the spread of Remdesivir counterfeits. The proposed methodology describes how block chain can be used in supply chain management. The paper consists of systematic literature review of technology, proposed technology and methodology. The implementation can use radio frequency identification (RFID) at the level of manufacturers, distributors, and sellers.